2016
DOI: 10.1097/tp.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Unique CD8+ T Cell–Mediated Immune Responses Primed in the Liver

Abstract: Background The liver immune environment is tightly regulated to balance immune activation with immune tolerance. Understanding the dominant immune pathways initiated in the liver is important since the liver is a site for cell transplantation, such as for islet and hepatocyte transplantation. The purpose of this study is to examine the consequences of alloimmune stimulation when allogeneic cells are transplanted to the liver in comparison to a different immune locale, such as the kidney. Methods We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…To determine if the observed in vivo allocytotoxicity is CD8 dependent, a cohort of WT recipients were treated with anti-CD8 mAb 12 d prior to the day 7 in vivo allocytotoxicity assay; depletion of recipient CD8 1 T cells significantly reduced allogeneic allocytotoxicity (p < 0.0001). This confirmed that in vivo allocytotoxicity is predominantly CD8 mediated and that low residual allocytotoxicity in WT hosts is likely Ab mediated, as previously reported (16). In contrast, Ja18 KO recipients do not produce significant alloantibody after transplant (44).…”
Section: Deficiency Of Inkt Cells In Hepatocellular Allograft Recipie...supporting
confidence: 90%
See 1 more Smart Citation
“…To determine if the observed in vivo allocytotoxicity is CD8 dependent, a cohort of WT recipients were treated with anti-CD8 mAb 12 d prior to the day 7 in vivo allocytotoxicity assay; depletion of recipient CD8 1 T cells significantly reduced allogeneic allocytotoxicity (p < 0.0001). This confirmed that in vivo allocytotoxicity is predominantly CD8 mediated and that low residual allocytotoxicity in WT hosts is likely Ab mediated, as previously reported (16). In contrast, Ja18 KO recipients do not produce significant alloantibody after transplant (44).…”
Section: Deficiency Of Inkt Cells In Hepatocellular Allograft Recipie...supporting
confidence: 90%
“…CD4-independent, CD8 1 T cellmediated allograft rejection is resistant to costimulatory blockade and implicated in the rejection of hepatocellular allografts (13,19), intestinal allografts (20), skin allografts (21,22), and cardiac allografts (23,24). In addition, we have reported that the liver microenvironment is sufficient to prime CD8 1 T cells in the absence of both CD4 1 T cells and secondary lymphoid tissue (16). Alloprimed CD4-independent CD8 1 T cells in hepatocyte allograft recipients are distinguished by TNF-aÀdependent cytotoxic effector function that peaks on day 5 posttransplant compared with CD4-dependent, CD8 1 T cellmediated Fas ligand (FasL) and perforin-dependent cytotoxicity that peaks on posttransplant day 7 (17,18).…”
mentioning
confidence: 86%
“…By virtue of their location (lining the walls of liver sinusoids), KCs interact routinely with circulating immune cells in the blood [17]. Such interactions, including that of infiltrating macrophages, may contribute to a broad dysfunction of the circulating CD8 + T-cell pool that we and others have observed in chronic HCV infection [18,19,20,21]. While impaired HCV-specific CD8 + T-cells pose an impediment to virus control in chronic infection, a broad dysfunction of the T-cell compartment suggests an influence from antigen-independent cell-to-cell interactions or local and systemic microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…Once anti-CD8 mAb treatment was stopped though, hepatocyte rejection occurred in all recipients by day 63 indicating that long-term engrafted hepatocytes remain vulnerable to (CD8-mediated) hepatocyte rejection. The occurrence of rejection 14 days after cessation of anti-CD8 mAb treatment was expected since this time-frame corresponds with reconstitution of CD8 + T cells in the periphery and transplanted hepatocytes are highly susceptible to CD8 + T cell mediated rejection (13, 4345). Our data is consistent with the interpretation that, despite the presence of high alloantibody titers (Figure 3C), transplanted allogeneic hepatocytes are not rejected in CD8-depleted recipients with impaired FcγR signaling.…”
Section: Resultsmentioning
confidence: 99%